RADIOIMMUNOTHERAPY IN THE TREATMENT OF MALIGNANCIES - V. I. Chernov; O. D. Bragina; I. G. Sinilkin; A. A. Titskaya; R. V. Zelchan (Сибирский онкологический журнал, 2016)
This review presents information about one of the promising areas of targeted therapy in modern oncology, which is called radioimmunotherapy. Particular attention is paid to the possibility of clinical application of this type of systemic treatment for patients with both hematologic malignancies and solid tumors.